2019
DOI: 10.4103/eus.eus_20_19
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in hepatopancreatobiliary EUS

Abstract: The last American College of Gastroenterology's (ACG) annual meeting was held in Philadelphia on October 5–10, 2018 and showcased a wide variety of the latest and upcoming research within the field of Gastroenterology. This article will present the advancements and research regarding endoscopic ultrasound (EUS) presented at this year's meeting with focus on hepatopancreatobiliary indications. Seventy studies related to EUS were presented; however, case reports and video forum presentations were excluded from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Hepatobiliary-pancreatic (HBP) cancer includes liver cancer, biliary tract cancer, gallbladder cancer and pancreatic cancer[ 1 - 3 ]. The number of new cases of HBP cancer worldwide in 2018 was approximately 1.85 million, accounting for 10% of all newly diagnosed cancer cases and resulting in a great financial burden[ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatobiliary-pancreatic (HBP) cancer includes liver cancer, biliary tract cancer, gallbladder cancer and pancreatic cancer[ 1 - 3 ]. The number of new cases of HBP cancer worldwide in 2018 was approximately 1.85 million, accounting for 10% of all newly diagnosed cancer cases and resulting in a great financial burden[ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The family in this case was definitively diagnosed with type 2 HHT, based on the Curacao standard[ 7 , 8 ]. This diagnosis relied on blood sample analysis of the proband and some relatives, which indicated the presence of an ACVRL1 mutation (c. 1232G>A, p. Arg411Gln) in the family, a history of epistaxis, and presence of capillary dilation of skin and mucosa, and AVM in the liver[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer is most commonly diagnosed via initial CT imaging; equivocal imaging results can often be clarified with EUS-FNA, which has been shown to have sensitivity and specificity greater than 90% [ 73 ]. Studies comparing EUS-FNA to cross-sectional imaging found that the former is especially accurate for diagnosing smaller pancreatic masses (<2 cm) [ 15 , 73 ].…”
Section: Diagnosis and Stagingmentioning
confidence: 99%
“…Additionally, the function of EUS in visualizing and sampling the gastrointestinal wall layers, peri-intestinal lymph nodes, and surrounding structures gives it a crucial role in locoregional staging of malignancies [ 9 , 13 , 14 ]. Finally, there is an ever-growing therapeutic role for EUS, from supplementing ERCP in stent placement for malignant obstruction, to delivering anti-tumor agents via fine needle injection (FNI) in pancreatic cancer [ 15 ].…”
Section: Introductionmentioning
confidence: 99%